GENETIC IMPROVEMENT AND DEVELOPMENT OF GENETIC STOCKS IN SUGARCANE THROUGH BACKCROSS BREEDING - Alarmelu, S; Pazhany, Adhini S; Jayabose, C (Journal of Sugarcane Research, 2019)
Broadening genetic base through backcross breeding is an effective approach to generate diverse genetic stocks for important economic traits coupled with red rot resistance. Three hundred backcross hybrids developed by backcrossing elite F1 clones (derived by utilizing improved clones (S.officinarum, S. robustum and S. barberi) with improved S. officinarum or improved S. robustum or Co canes showed variability for the traits studied. Heritability estimates varied over the different nobilising generations and study indicated that selection of parents for sucrose % during the nobilisation process will be effective. BC1 and BC2 hybrids developed from improved S. robustum x improved S. officinarum showed an improvement of 16.71% and 34.09%: 22.36% and 40.58% for sucrose % at 360 days in comparison with improved S. officinarum and S. robustum parents, respectively. Crosses with PIR 96-285 and PIR 001188 as one of backcross parents generated high quality recombinants. The introgression of new genes provided backcross progenies with redrot resistance. The prebred clones expressed wide variability for various traits like internode colour, cane thickness, leaf colour, canopy, hairiness, cane yield and quality characters. Among the pre bred materials, 26 clones recorded single cane weight > 1.25 kg, 45 clones with brix % above 20% and 41 clones with juice sucrose above 18.5% and most of them were derived from the crosses involving improved S.officinarum x improved S. robustum parents back crossed to improved S. officinarum or Co canes. Elite trait specific BC1 hybrids viz., 13-69, 13-251, 13-103, 13-208, 13-253, 14-57 and 14-60 and BC2 hybrids viz.,14-42, 14-66,Â 14-161 combining good quality and yield traits coupled with red rot resistance: 13-57, 13-114, 13-147 and 13-251, 14-76, 14-69, 14-163 and 14-174 with thickness and resistance to red rot can be utilized in sugarcane varietal improvement programmes.